The ethics of animal research: a survey of the public and scientists in North America. Issue 1 (December 2016) - Joffe, Ari; Bara, Meredith; Anton, Natalie; Nobis, Nathan
Abstract Background To determine whether the public and scientists consider common arguments (and counterarguments) in support (or not) of animal research (AR) convincing. Methods After validation, the survey was sent to samples of public (Sampling Survey International (SSI; Canadian), Amazon Mechanical Turk (AMT; US), a Canadian city festival and children's hospital), medical students (two second-year classes), and scientists (corresponding authors, and academic pediatricians). We presented questions about common arguments (with their counterarguments) to justify the moral permissibility (or not) of AR. Responses were compared using Chi-square with Bonferonni correction. Results There were 1220 public [SSI, n = 586; AMT, n = 439; Festival, n = 195; Hospitaln = 107], 194/331 (59 %) medical student, and 19/319 (6 %) scientist [too few to report] responses. Most public respondents were <45 years (65 %), had some College/University education (83 %), and had never done AR (92 %). Most public and medical student respondents considered 'benefits arguments' sufficient to justify AR; however, most acknowledged that counterarguments suggesting alternative research methods may be available, or that it is unclear why the same 'benefits arguments' do not apply to using humans in research, significantly weakened 'benefits arguments'. Almost all were not convinced of the moral permissibility of AR by 'characteristics of non-human-animals arguments', including that non-human-animals are not sentient, or are property. Most were not convinced of the moral permissibility of AR by 'human exceptionalism' arguments, including that humans have more advanced mental abilities, are of a special 'kind', can enter social contracts, or face a 'lifeboat situation'. Counterarguments explained much of this, including that not all humans have these more advanced abilities ['argument from species overlap'], and that the notion of 'kind' is arbitrary [e.g., why are we not of the 'kind' 'sentient-animal' or 'subject-of-a-life'?]. Medical students were more supportive (80 %) of AR at the end of the survey (p < 0.05). Conclusions Responses suggest that support for AR may not be based on cogent philosophical rationales, and more open debate is warranted.